Functional thinking style and its contribution to learn the accuracy of block and smash serve in volleyball among university students - Ayad Ali Hussein Saeed; Haider Abdul Amir Habib; Esraa Fouad Saleh (Universidad de Murcia, 2023)
Article accepted. The article will be published here soon. Pending final quality checks.